Acute Compartment Syndrome: Do guidelines for diagnosis and management make a difference?. Issue 9 (September 2018) - Bodansky, D.; Doorgakant, A.; Alsousou, J.; Iqbal, H.J.; Fischer, B.; Scicluna, G.; Bowers, M.; Narayan, B.
Abstract: Background: The best outcomes following Acute Compartment Syndrome (ACS) are attributed to early diagnosis and treatment. National guidelines were issued in the United Kingdom in 2014 (BOAST 10) to standardise and improve management. We analysed standards of diagnosis and management before and after the introduction of the guidelines. Methods: We retrospectively reviewed the data of all patients with ACS requiring fasciotomy between March 2010 and May 2015 across four Major Trauma Centres (MTCs) in the Northwest of England. We analysed the pooled data for variations between the centres and the effect of BOAST10 implementation. Results: 75 fasciotomies were recorded, with trauma being the cause in 42 cases (56%). The commonest site was the leg (44, 59%) followed by the forearm (15, 20%). The median time from decision to operate to fasciotomy was 2 h (range 0–6) and thereafter a median of 2 days (1–7) until a second visit. The practice across the four centres was similar up to diagnosis and treatment, but there was significant variation in practice after fasciotomy. The BOAST guidelines did not improve the time to surgery, time to second visit nor the recording of clinical signs. 21 patients had severe complications, including one death and 4 amputations. Conclusions: There continues to be significant variability in the definitive management of ACS. National guidelines do not appear to make a discernible impact on practice, and additional methods of ensuring safe management of this critical condition seem warranted.